Cardamine kuankuoshuiense (Brassicaceae), a new species from Guizhou, China - An, Ming-Tai; Lin, Yun; Yu, Li-Fei; Yang, Yan-Bin; Cheng, Guang-Ping; Li, Ji-Qiang (Phytotaxa, 2016)
A new species of the genus Cardamine Linn.(Brassicaceae), Cardamine kuankuoshuiense M. T. An, Yun Lin & Y. B. Yang is described, illustrated and photographed from Suiyang County, Guizhou Province, SW China. This species was found growing on damp precipice or between moist rock crevices in evergreen broad-leaved forests or mixed needle-leaved and evergreen broad-leaved forests in carst mountains at altitudes of 1400–1430 m. The new species is related to both Cardamine griffithii J. D. Hook. & Thomson and Cardamine multijuga Franch., but differs from both of them by herbs 15–25 cm tall, scapose, with a few stolons, stems terete, cauline leaves absent.